2005
DOI: 10.7202/705397ar
|View full text |Cite
|
Sign up to set email alerts
|

Revue sur l'enlèvement des métaux des effluents par adsorption sur la sciure et les écorces de bois

Abstract: Les résidus de transformation du bois tels les écorces et la sciure de bois ont été largement étudiés depuis quelques années pour leur propriété d'adsorption et d'enlèvement des métaux toxiques contenus dans les effluents contaminés. En ce qui concerne la sciure de bois, les recherches répertoriées ont porté principalement sur l'utilisation du sapin rouge, du manga, du tilleul, de l'épinette, du pin, du cèdre, du teck, de l'akamatsu et du buna. Pour ce qui est des écorces de bois, plusieurs espèces ont été étu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
7
0
3
Order By: Relevance
“…In fact, the adsorption efficiency obtained with 5 g/L of solid/liquid ratio was 74 %; however, for 10, 20 and 30 g/L it was 96, 98 and 99 % respectively. The results are in agreement with similar previous study for heavy metal adsorption (Bouchemal and Achour 2007;Fiset et al 2001). However, the adsorption capacity (q e ) decreases as adsorbent dosage increases (Fig.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 83%
See 2 more Smart Citations
“…In fact, the adsorption efficiency obtained with 5 g/L of solid/liquid ratio was 74 %; however, for 10, 20 and 30 g/L it was 96, 98 and 99 % respectively. The results are in agreement with similar previous study for heavy metal adsorption (Bouchemal and Achour 2007;Fiset et al 2001). However, the adsorption capacity (q e ) decreases as adsorbent dosage increases (Fig.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 83%
“…At high temperature and due to the large kinetic energy of particles, in the earlier time the possibility of collision between metal and adsorbent sites is higher; however, when reaching equilibrium the probability of collision and consequently fixation of metal ions become unprivileged because majority of sites on surface are occupied. As well, it was observed that at high temperature, adsorption sites can be subject to destruction or solubilization like the tannin onto sawdust as reported in Fiset et al (2001) revue and so the adsorption phenomenon is disfavored.…”
Section: Effect Of Temperature and Stirring Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…On peut citer les biomasses algales (AKSU, 2005), la tourbe (McKAY, 1996) ou encore les déchets issus de l'industrie du bois (FISET et al, 2000). L'amidon fait également l'objet de nombreuses études dans la littérature.…”
Section: Introductionunclassified
“…Adsorption has gained importance over other techniques such as precipitation, ion exchange, filtration or solvent extraction due to its good performance for removing contaminants from industrial effluents. On the other hand, there has been a constant search for new adsorbents among industrial and agricultural residues with high adsorption capacity and selectivity, abundant in nature and cheap (Bailey et al, 1999;Ho and McKay, 1999;Fiset et al, 2000;Calace et al, 2002;Rao and Viraraghavan, 2002).…”
Section: Introductionmentioning
confidence: 99%